THE SIGNIFICANCE OF LYRIC GENRES IN THE SYNCRETISM OF ENGLISH AND UZBEK LITERATURE (SCIENCE TIME JOURNAL, 2023)
The main image of the lyric is considered a lyrical hero. In the lyrics, the inner world of the lyrical hero comes first. All expression passes through the "I" of the poet. In the lyrics, unlike the epic, there will be no specific epic plot. What stands out from the dramatic type is the strong subjectivity of the Lyric. The article discusses the main features of lyrics in English and Uzbek literature.